Respostas de café conilon à concentração de ferro - Campos, Luana Morati (2014)
Iron (Fe) is an essential element for the growth and development of plants. However, it is often present in groundwater used for irrigation at concentrations that may cause phytotoxicity over time. In this study, the effect of doses of Fe on root growth, mineral concentration of leaves, electrolyte leakage, photosynthetic pigments content, photosynthesis, leaf and root anatomy and toxicity symptoms in plants of Coffea canephora Pierre ex A. Froehner cv. Conilonwas investigated. The seedlings were treated for 30 days by the addition of 0 (control), 10, 40, 120, 200 and 400 mg/L of FeSO4.7H2O provided as Fe EDTA more salt in the soil. The dry mass of roots showed lower values under the highest dose of Fe. Plants under the highest dose of Fe showed higher leaf accumulation of this element.The higher content of boron(B) occurred in individuals at the dose of 400 mg/L compared to the doses of 40 mg/L and 200 mg/L. Phosphorus (P) contents did not differ and werelower at the doses of 120, 200 and 400 mg/L Fe when compared to control.The leaf potassium (K) concentrations were higher at 10, 40, 120, 200 and 400 mg/L Fe. The highest zinc (Zn) leaf contentswere found in plants subjected to120, 200 and 400 mg/L of Fein relation to the control and the dose of 10 mg/L of Fe. Electrolyte leakage was higher in plants under 400 mg/L of Fe compared to dose of40 mg/L, however didnot differfrom the others doses. There was no significant difference in the levels of photosynthetic pigments and parameters of chlorophyll a. The control plants showed higher photosynthesis, stomatal conductance and transpiration, and the lowest rates were found at 200 mg/L Fe. Internal carbonconcentrationwas higher in plants under 400mg/L of Fe. Necrosis was observed in mature leaves under higher dose of Fe. Adaxial epidermis,spongy parenchymaand limbthicknessdid not show differences between the different treatments. The palisade parenchyma thickness was lower at 400 mg/L comparedto the doses of 120 and 200 mg/L andadaxial epidermisthickness was highercomparedto the dose of 40 mg/L. In the treatment with higher Fe content there was a change in the morphology of roots,such as reduced growth and emission of lateral roots. There was also an increased lignification of the epidermis and cortex; some cortical cells showed format changes, with protoplast retraction. Overall, the results indicate that the dose of 400 mg/L Fe is harmful, affecting thestructure and functionality of Conilon variety